Luteal phase decrease in packed cell volume in healthy non‐pregnant and pregnant bitches - Rachel Moxon; Rebekah Dutton Worsfold; Julie Davis; Wendy Adams; Gary C. W. England (Veterinary Medicine and Science, 2023)
Abstract Objectives To establish packed cell volume (PCV) ranges for non‐pregnant, pregnant and post‐partum bitches from day 10 of proestrus, investigating any relationship with parity and litter size. Methods This prospective cohort study used 37 healthy breeding bitches to examine PCV counts from routine blood samples collected every 4 weeks, from day 10 of proestrus, as part of routine PCV monitoring. Results For pregnant (n = 19) and non‐pregnant (n = 18) bitches, PCV decreased until week 8 (corresponding to 8.5 ± 1.1 days before whelping for pregnant bitches) and recovered by 16–20 weeks after the initial sample; bitches that whelped average and large litters showed greater declines. PCV began to recover sooner for bitches that had previously whelped one or two litters compared to bitches that had previously whelped three or more litters. There was a significant three‐way interaction between time after the onset of proestrus, litter size and the number of previous litters which demonstrated that the large decrease in PCV for bitches that had previously whelped three or more litters only occurred in bitches that were expecting an average or large sized litter. Clinical Significance Chronological variation in PCV for pregnant and non‐pregnant bitches was established during the reproductive cycle. There was no evidence to suggest that routine PCV measurement for normal, healthy bitches would be beneficial. However, knowledge from this study may be useful when deciding whether to prospectively monitor a bitch where there is a history of previous pregnancy‐related anaemia, when performing a caesarean section due to the anticipated blood loss during surgery, or when examining blood profiles for post‐litter bitches.